(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The principal economic categories and the description of creation development at the enterprise leader are considered in the article, the structure of creative type manager potential is described, the conception of creative manager potential is grounded, the factors of creative leader successful formation are discovered.